Emotional symptoms and inflammatory biomarkers in childhood: Associations in two Australian birth cohorts - Lange, Katherine; Pham, Cindy; Fedyszyn, Izabela E; Cook, Fallon; Burgner, David P; Olsson, C; Downes, Marnie; Priest, Naomi; Mansell, Toby; Tang, Mimi L K; Ponsonby, Anne-Louise; Symeonides, Christos; et al. (My University, 2024)
An increasing body of evidence supports associations between inflammation and mental health difficulties, but the onset and directionality of these relationships are unclear. Data sources: Barwon Infant Study (BIS; n = 500 4-year-olds) and Longitudinal Study of Australian Children (LSAC; n = 1099 10-13-year-olds). Strengths and Difficulties Questionnaire emotional symptoms at 4, 10-11 and 12-13 years, and circulating levels of two inflammatory biomarkers, high-sensitivity C-reactive protein (hsCRP) and glycoprotein acetyls (GlycA), at 4 and 11-12 years. Adjusted quantile regression models examining cross-sectional associations between emotional symptoms and inflammation in 4-year-olds (BIS), and cross-lagged associations in 10-13-year-olds (LSAC). We identified a small association between higher emotional symptoms at 10-11 years and higher GlycA levels a year later (standardised coefficient β = 0.09; 95%CI: 0.02 to 0.15). Sex-stratified analyses revealed this association was stronger for boys (β = 0.13; 95%CI: 0.04 to 0.21) than girls (β = 0.01; 95%CI: -0.09 to 0.11). These associations were not observed for hsCRP. There was little evidence of an association between higher GlycA or hsCRP at 11-12 years and emotional symptoms a year later, or cross-sectional associations between emotional symptoms and hsCRP or GlycA at 4 years. A single time-point of biomarker collection in late childhood precluded adjustment for baseline inflammatory biomarkers. Our results support the direction of association from emotional symptoms to inflammation in late childhood, with potential sex differences. This adds to the body of evidence that addressing emotional symptoms in childhood is a major priority in optimising overall health throughout the life course.
Keywords: Childhood; GlycA; Inflammation; Longitudinal; Mental health; hsCRP; Adolescents and youth; Health and wellbeing